Governing Net Zero Carbon Removals to Avoid Entrenching Inequities - Healey, Peter; Scholes, Robert; Lefale, Penehuro; Yanda, Pius (Frontiers in Climate, 2021)
• Climate change embeds inequities, and risks reinforcing these in policies for remediation. In particular, with CDR in ‘Net-zero’ policies: o Offsets may be considered inequitable if seen to avoid or delay reductions. o Offsets to emissions through technologically mature methods of CDR require natural resources at scales threatening food security; o Knowledge of the potential of immature CDR is largely a global north monopoly; o CDR in particular environments is ill-understood and its implications for development unexamined; • Robust progress can only be achieved through global agreement on: o Simultaneously reduce emissions and enhance removals; o Equity in burden-sharing; o An interdisciplinary effort led by individual jurisdictions and focused on the co-development of technologies and governance to create CDR portfolios matched to local needs.